EKSISTENSI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MINAT BELAJAR SISWA - I Ketut Ngurah Ardiawan; Luh Sukertiasih (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The learning process is said to be successful if students get maximum results. Maximum results depend on the extent to which students' interests and motivations are encouraged to take part in learning. Interest and motivation can be grown by several factors, one of which is learning media. Learning media are said to be able to attract students 'learning interest because learning media can attract students' attention, activate students in learning activities, and can concrete abstracts. Therefore it is necessary for the development of instructional media carried out by teachers as educators, so that the learning process can achieve the desired goals.Keywords: Learning Media, Learning Interest, Learning Process